Recent Advances of Ceria‐Based Materials in the Oxidation of Carbon Monoxide. Issue 2 (16th November 2020) - Dong, Chenxi; Zong, Xupeng; Jiang, Wenshuai; Niu, Lijuan; Liu, Ziwen; Qu, Dan; Wang, Xiayan; Sun, Zaicheng
Abstract : Carbon monoxide (CO) is a toxic and harmful gas pollutant. The realization of low‐temperature CO oxidation has been the focus of research. Also, CO oxidation as a typical model reaction is conducive to the in‐depth study of the catalytic reaction mechanism. Due to its unique oxygen storage/release capacity (OSC) and the easy transition between Ce 3+ and Ce 4+, CeO2 is widely used as a catalyst and catalyst support in many important reactions, especially the low‐temperature CO oxidation reaction. Herein, the application of cerium‐based materials in low‐temperature CO oxidation and CeO2 activity enhancement strategies in recent years are elaborated upon, including metal loading, adjustment of exposed facets of CeO2, and metal doping, through metal‐support interaction and the generation of oxygen vacancies on the CeO2 surface to improve the CO oxidation activity of cerium‐based catalysts. At the end of the review, the synthesis of Ce‐based materials and their applications and challenges in the field of CO oxidation are looked at. Abstract : Ceria is an excellent supporter of the catalyst for low‐temperature CO oxidation due to its unique oxygen storage/release capacity. Herein, the catalyst is summarized in two ways: metal/ceria and doped ceria. Metal cluster catalysts cooperate with ceria with oxygen vacancy, mainly following the Mars–van Krevelen model, and doped ceria tends to obey the Langmuir–Hinshelwood model.